Multigene phylogenetics of euglenids based on single-cell transcriptomics of diverse phagotrophs - Lax, G.; Kolisko, M.; Eglit, Y.; Lee, W.J.; Yubuki, N.; Karnkowska, A.; Leander, B.S.; Burger, G.; Keeling, P.J.; Simpson, A.G.B. (Molecular phylogenetics and evolution, 2021)
[Display omitted] •First multigene phylogeny of euglenids to include phagotrophs (and symbiontids).•Symbiontids are an independent branch within Euglenozoa, not derived euglenids.•Petalomonads inferred to be the sister group to all other euglenids.•Robust support for a Spirocuta plus Olkasia clade (new taxon Olkaspira).•A clade including Ploeotiidae, Lentomonas and Keelungia shown (new taxon Alistosa). Euglenids are a well-known group of single-celled eukaryotes, with phototrophic, osmotrophic and phagotrophic members. Phagotrophs represent most of the phylogenetic diversity of euglenids, and gave rise to the phototrophs and osmotrophs, but their evolutionary relationships are poorly understood. Symbiontids, in contrast, are anaerobes that are alternatively inferred to be derived euglenids, or a separate euglenozoan group. Most phylogenetic studies of euglenids have examined the SSU rDNA only, which is often highly divergent. Also, many phagotrophic euglenids (and symbiontids) are uncultured, restricting collection of other molecular data. We generated transcriptome data for 28 taxa, mostly using a single-cell approach, and conducted the first multigene phylogenetic analyses of euglenids to include phagotrophs and symbiontids. Euglenids are recovered as monophyletic, with symbiontids forming an independent branch within Euglenozoa. Spirocuta, the clade of flexible euglenids that contains both the phototrophs (Euglenophyceae) and osmotrophs (Aphagea), is robustly resolved, with the ploeotid Olkasia as its sister group, forming the new taxon Olkaspira. Ploeotids are paraphyletic, although Ploeotiidae (represented by Ploeotia spp.), Lentomonas, and Keelungia form a robust clade (new taxon Alistosa). Petalomonadida branches robustly as sister to other euglenids in outgroup-rooted analyses. Within Spirocuta, Euglenophyceae is a robust clade that includes Rapaza, and Anisonemia is a well-supported monophyletic group containing Anisonemidae (Anisonema and Dinema spp.), ‘Heteronema II’ (represented by H. vittatum), and a clade of Neometanema plus Aphagea. Among ‘peranemid’ phagotrophs, Chasmostoma branches with included Urceolus, and Peranema with the undescribed ‘Jenningsia II’, while other relationships are weakly supported and consequently the closest sister group to Euglenophyceae remains unresolved. Our results are inconsistent with recent inferences that Entosiphon is the evolutionarily pivotal sister either to other euglenids, or to Spirocuta. At least three transitions between posterior and anterior flagellar gliding occurred in euglenids, with the phylogenetic positions and directions of those transitions remaining ambiguous.